The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fonc.2022.1069378
|View full text |Cite
|
Sign up to set email alerts
|

The immune checkpoint expression in the tumor immune microenvironment of DLBCL: Clinicopathologic features and prognosis

Abstract: Background & aimsThe immune checkpoint recently provides a new strategy for the immunotherapy of malignant tumors. However, the role in the immune microenvironment of DLBCL is not completely clear.MethodsWe detected the expression of PD-1, LAG-3, TIM-3, and TIGIT on TILs and on tumor cells among 174 DLBCL patients by IHC.ResultsIn TILs, the positive rates of PD-1, LAG-3, TIM-3 and TIGIT were 79.3%, 78.8%, 62.7% and 69.5%, respectively.TIM-3 and TIGIT were expressed in 44.8% and 45.4% of tumor cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Lymphocytes are important mediators of antibody-dependent cell-mediated cytotoxicity, and lymphopenia is an indicator of poor prognosis in DLBCL due to the reduced tumor clearance and surveillance ability of the host ( 19 ). An increased level of monocytes in the peripheral blood can promote tumor progression by increasing angiogenesis, inhibit anti-tumor immunity, and increase the proliferation of malignant cells ( 20 ). A low LMR favors tumorigenesis and progression by increasing the levels of cytokines released by tumor cells, such as granulocyte colony-stimulating factor.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes are important mediators of antibody-dependent cell-mediated cytotoxicity, and lymphopenia is an indicator of poor prognosis in DLBCL due to the reduced tumor clearance and surveillance ability of the host ( 19 ). An increased level of monocytes in the peripheral blood can promote tumor progression by increasing angiogenesis, inhibit anti-tumor immunity, and increase the proliferation of malignant cells ( 20 ). A low LMR favors tumorigenesis and progression by increasing the levels of cytokines released by tumor cells, such as granulocyte colony-stimulating factor.…”
Section: Discussionmentioning
confidence: 99%
“…Another report showed the costimulatory interactions between malignant B-cells and T-cells in human DLBCL, and the coinhibitory signals mediated by immune checkpoint seemed to be the main driving force for T cell exhaustion [ 46 ]. In addition, it was reported that immune cells in the tumor microenvironment were associated with the outcome in human DLBCL [ 3 , 26 , 45 ]. The studies indicated that patient prognosis was correlated with the abundance of tumor-infiltrating T-cells and their subsets.…”
Section: Discussionmentioning
confidence: 99%
“…The studies indicated that patient prognosis was correlated with the abundance of tumor-infiltrating T-cells and their subsets. Furthermore, patients with a high percentage of immune checkpoint-positive T cells had a worse prognosis [ 3 , 26 , 45 ]. Transcriptomic analysis revealed the overexpression of immunosuppressive factors and inflammatory chemokines in relapsed/refractory DLBCL cases when compared to chemotherapy-sensitive DLBCL cases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“… 13 In this same study, PD-1 was significantly increased on CD8 T cells only (not CD4-positive T cells). Ma et al 17 performed immunohistochemical analysis of 174 DLBCL cases and found that 69.5% and 45.4% showed TIGIT expression on the TILs and lymphoma cells, respectively. This team also found no association between TIGIT expression on lymphoma cells or TILs and survival.…”
Section: Discussionmentioning
confidence: 99%
“…For TIGIT immunohistochemistry, there is no uniform scoring system. Ma et al 17 used a cutoff of 20% positivity in tumor or TILs to categorize each compartment as TIGIT-positive. Others have used graded approaches where <5% to 10% positivity (based on representative images) were used 15 .…”
Section: Methodsmentioning
confidence: 99%